Discrimination against black people in the story «La emplazada» - Vasquez Delgado, Gino Joaquin (2021)
In this article I will analyse the cases of discrimination and racism towards Afro-descendants that are so far very recurrent in our country and in the world. To this end, I will address the story «La emplazada», a text in which Ricardo Palma refers to discrimination, slavery and racism in the seventeenth century.